You are on page 1of 4

Short summary of the 1st week of Electrodynamics I

Toshihiko Ota1,
Yachay Tech, Hacienda San Jose s/n y Proyecto Yachay, 100119 San Miguel de Urcuqu, Ecuador
(Dated: September 8, 2017)

When you find typos and mistakes, please let me know.


The Levi-Civita symbol is defined as

1, for (i, j, k) = (1, 2, 3), (2, 3, 1), (3, 1, 2),
ijk = 1, for (i, j, k) = (1, 3, 2), (2, 1, 3), (3, 2, 1), (1)

0, otherwise, e.g., (i, j, k) = (1, 1, 2).

Using this, you can express cross products of vectors as

ei ej = ijk ek , AB= ijk ei Aj Bk , (2)
k=1 i,j,k=1

where e1 = ex , e2 = ey , e3 = ez , and A1 = Ax etc. Why do we introduce this? Because we are, at least I am too
lazy to write all the elements of vector. Expressing vectors with indices and using Levi-Civita symbol, we can express
cross products in shorthand. For example, you can prove curl(gradf ) = 0 without writing all the elements;
3 [ ]
curl(gradf ) = (f ) = ijk ei
xj xk

Note that x1 = x, x2 = y, x3 = z.


= ikj ei f
xk xj

Here I exchanged the names of the indices Now I call j as k and call k as j.


= ijk ei f
xk xj

Here we used ikj = ijk .

= curl(gradf ). (3)
This means
curl(gradf ) = 0. (4)
Please do the same calculation by writing explicitly all the components. Then, you will find this is nicer (at least,
you do not need to move your hands so much). You can prove div(rotA) = 0 in the same way.
There is a useful identity, which is

Electronic address:


ijk klm = il jm im jl , (5)

You can show this by putting concrete numbers in i, j, l, and m and compare the LHS with the RHS. (cf. Problems
in Sec. 6 of Griths 3rd ed. and the Wikipedia article Levi-Civita symbol). With this identity, you can show

A (B C) = (A C)B (A B)C (6)

in 5 lines You do not need to memorize this formula! Please show Eq. (6) using Eq. (5) by yourself and get use to
express vectors with indices and calculate cross products with Levi-Civita symbols. I will use this kind of shorthand
and basically will not write all the components of vectors explicitly in the lecture It is tiresome and the space of
whiteboards is limited.


We sometimes/often need to express vectors in the other coordinates than Cartesian. Therefore, we also need to
express the nabla operator in the other coordinate than Cartesian. You do not need to memorize it I do not
recommend it. I rather recommend that you understand how to derive it.
You know nabla in Cartesian coordinate, which is

ex + ey + ez . (7)
x y z

What is nabla, for example, in spherical coordinates? You know the relations between the variables (x, y, z) in
Cartesian and those (r, , ) in spherical coordinates, which are

x = r sin cos , y = r sin sin , z = r cos . (8)

You also know the relations between the basis vectors in both the coordinates, which are1

er =ex sin cos + ey sin sin + ez cos , (9)

e =ex cos cos + ey cos sin ez sin , (10)
e = ex sin + ey cos . (11)

Substituting these relations Eqs. (9)-(11) of the basis vectors into Eq. (7)2 , and using the chain rule

= + + , also for y and z, (12)
x x r x x
you can obtain nabla in spherical coordinates. The calculation is straightforward, but lengthy, tiresome, boring, and
not so beautiful. There is a smart short cut.
If you are familiar with total derivative df of a function f (qi ) in terms of the variables qi , which is defined as
df = dqi , (13)

1 The derivation of Eqs. (9)-(11) was shown in the exercise class.

2 First, you have to solve the simultaneous equations Eqs. (9)-(11) in terms of ex,y,z , and substitute ex,y,z into Eq. (7).

you can explicitly see that the total derivative df is given with the dot product of the gradient of f and the infinitesimal
displacement vector dr in Cartesian coordinate:
df = (f ) dr. (14)
The important point is, this expression does not depend on the choice of coordinates (Griths calls this gradient
theorem. See Sec. 1.3.3).
Let us express the total derivative df in spherical coordinates. We do not know the gradient of f in spherical
coordinates That is what we want to derive. Here we give it as
f = er (f )r + e (f ) + e (f ) , (15)
and we will derive (f )r,, . What is the displacement vector in polar coordinate? The displacement vector is noting
but the total derivative of a position vector r. So we can calculate it as3
dr =d(r) = d(er r)
=(der )r + er dr
Here we used Leibniz rule (product rule) of derivative
( )
er er
= d + d r + er dr

See Eq. (9) er is a function of and . The definition of total derivative is given at Eq. (13)
=er dr + e rd + e r sin d. (16)
Substituting Eqs. (15) and (16) into Eq. (14), we have
df = (f )r dr + (f ) rd + (f ) r sin d. (17)
From the definition Eq. (13) of total derivative, we also have
f f f
df = dr + d + d. (18)
Comparing Eq. (17) and Eq. (18), we can read
(f )r = , (19)
(f ) r = , (20)

(f ) r sin = , (21)

(f )r = , (22)
1 f
(f ) = , (23)
1 f
(f ) = . (24)
r sin
Substituting back Eqs. (22)-(24) to Eq. (15), we have
f 1 f 1 f
f = er + e + e . (25)
r r r sin
This means,

3 You can also know the displacement vector by drawing it, without doing this calculation, if you are good at drawing...

1 1
= er + e + e . (26)
r r r sin

This is what we want to know nabla expressed with the variables and the basis vectors of a spherical coordinate.
You can find this in Wikipedia article Del in cylindrical and spherical coordinates. In the same way, you can also
derive nabla in cylindrical coordinates.